(untitled) (Per Musi, 2010)
The article discusses Axé music providing elements in an attempt to deconstruc three myths related to it: monoculture, low technical quality and its decadence. The method used focuses on content analysis, departing from verification of data collected through semi- structured interviews with musicians, technical staff, producers and musicbusiness executives from Salvador (Brazil), along with documental research related to the musical scene of Bahia today.